Development and validation of a novel short-form nutrition literacy measurement tool for Chinese college students - Guangju Mo; Guangju Mo; Siyue Han; Tianjing Gao; Qing Sun; Min Zhang; Huaqing Liu (Frontiers Media S.A., 2022)
ObjectivesTo develop and validate a short-form nutrition literacy (NL) assessment tool for Chinese college students based on a 43-item NL measurement scale.MethodsTo develop and validate short-form NL scale, 1359 college students were surveyed, the data were analyzed using exploratory factor analysis, linear regression analysis, Item analysis, confirmatory factor analysis, and Pearson correlation.ResultsThe 12-item short-form NL scale (NL-SF12) was developed using factor analysis and regression analysis, which accounted for 96.4% of the variance. The correlation coefficient between the NL-SF12 and NL-43 was 0.969, indicating satisfactory criterion-related validity. The NL-SF12 had a Cronbach's α of 0.890, suggesting strong internal consistency reliability, and content validity index was greater than 0.9, indicating that each domain accurately reflects the connotation of nutrition literacy. The model-data fit and convergent validity of the confirmatory factor analysis results were both good.ConclusionThe NL-SF12 is an effective measurement tool with a good reliability and acceptable validity to assess comprehensively NL for college students, and is applicable to quick, widespread use in population study and practice with low respondent burden.